2008
DOI: 10.1007/s11095-008-9632-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Substrates and Inhibitors for the In Vitro Assessment of Bcrp Mediated Drug–Drug Interactions

Abstract: Data suggest different modes of substrate and inhibitor binding to Bcrp. In order to not overlook potential drug-drug interactions when testing drug candidates for inhibitory potential towards Bcrp, distinct Bcrp probe substrates should be used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 30 publications
4
60
0
Order By: Relevance
“…With use of mouse bcrp1-transfected cells, Ko143 gave a dose-dependent increase in Hoechst 33342 accumulation with an IC 50 of 0.15 M, similar to the previously reported values for bcrp inhibition (Allen et al, 2002;Muenster et al, 2008). Furthermore, the net secretion of ciprofloxacin was completely abolished by the specific BCRP inhibitor Ko143, in contrast with the partial inhibition evident with CsA and DIDS, P-gp/BCRP, and anion exchange inhibitors, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…With use of mouse bcrp1-transfected cells, Ko143 gave a dose-dependent increase in Hoechst 33342 accumulation with an IC 50 of 0.15 M, similar to the previously reported values for bcrp inhibition (Allen et al, 2002;Muenster et al, 2008). Furthermore, the net secretion of ciprofloxacin was completely abolished by the specific BCRP inhibitor Ko143, in contrast with the partial inhibition evident with CsA and DIDS, P-gp/BCRP, and anion exchange inhibitors, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…Likewise, polarized transcellular assays are not suitable for low permeable compounds, since they do not sufficiently penetrate the cells and therefore do not reach the export protein, potentially resulting in false-negative results. The existence of multiple binding sites on transport proteins could also add to the complexity of identifying substrate and inhibitor molecules in in vitro assay systems, leading to incorrect interpretation (Muenster et al, 2008;Giri et al, 2009). Careful selection of substrates and inhibitors is therefore critical for designing definitive studies, and may circumvent the current issues with very high experimental interlaboratory variability in in vitro assays .…”
Section: Lowmentioning
confidence: 99%
“…Examples are a wide range of anticancer drugs, sulfate and glucuronide conjugates of xenobiotics, tyrosine kinase inhibitors (TKIs), statins, fluorescent dyes and flavonoids [10,63] . In vitro assays showed that ABCG2 might have more than two binding sites, since ABCG2 inhibitors displayed different inhibition profiles, depending on the tested substrate [71][72][73] . For instance, the inhibitor Ko143 inhibited the transport of all the substrates tested by Giri et al [72] , which suggested its binding to a region that allosterically inhibits the transport of these substrates.…”
Section: Breast Cancer Resistance Proteinmentioning
confidence: 99%
“…However, the ABCG2 inhibitors elacridar, nelfinavir and Pluronic P85 seemed to bind to a different region, which inhibited the transport of the nucleoside analogs abacavir and zidovudine, but showed no or a partial effect on the transport of prazosin and imatinib. Muenster et al [73] showed that two different substrates, such as topotecan and albendazole sulfoxide, could simultaneously be transported without hindering each other's transport, which also suggest multiple binding sites in ABCG2. Furthermore, using homology modeling a complete homodimer ABCG2 model was created based on the crystal structure of the bacterial multidrug exporter Sav1866, which also suggested a multiple binding site [74] .…”
Section: Breast Cancer Resistance Proteinmentioning
confidence: 99%